A Comparative Study On The Energy Policies In Japan And Malaysia In Fulfilling Their Nations Obligations Towards The Kyoto Protocol - Lee, Keat Teong (Universiti Sains Malaysia, 2009)
Global warming and the associated changes in the world climate pattern have been accepted world wide as the gravest threat to humanity in the 20th century. To mitigate the impacts of global warming, the Kyoto Protocol was established in 1997 with the objective of reducing global greenhouse gases (GHGs) emission, in particular carbon dioxide (C02), by 5.2% below 1990 levels. Developed nations that ratified the Protocol are committed to GHG reduction targets while developing nations are encouraged to reduce GHG emissions on a voluntary basis.